Enhanced electrochemical performance of polycrystalline NCM811 cathode at high voltage through Te-doped LiNbO3 coating for lithium-ion batteries - Mohamed M. Abdelaal; Mohammad Alkhedher (Next Energy)
Ni-rich oxides with layered structures are considered promising cathode materials for high-voltage lithium-ion batteries due to their high capacity and wide potential window. However, they suffer from volume expansion and contraction, as well as Ni reactivity with electrolyte components, leading to structural degradation and continuous lithium consumption during cycling. In this study, a highly electrically and ionically layer of Te-doped LiNbO3 is coated onto the surface of LiNi0.8Co0.1Mn0.1O2 (NCM811) to protect the crystal structure from cracks and side reactions with the electrolyte at high voltages (4.3 V vs. Li/Li+). Characterization techniques, including X-ray diffraction (XRD), dynamic light scattering (DLS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and electrochemical impedance spectroscopy (EIS), are employed to analyze the structure, morphology, and electrochemical performance of the coated materials. Results show that the delivered capacity at 0.1 C increases from 192.9 to 210.8 mAh g−1 and the capacity retention at 0.2 C increases from 79.7 to 89.2% after 100 cycles. Moreover, the diffusion coefficient of the coated NCM is 4.6 × 10−13 cm2 s−1, while that of bare NCM is only 1.5 × 10−13 cm2 s−1 due to the reactivity of the coating layer with lithium. These findings provide valuable insights into the design and optimization of cathode materials for next-generation energy storage systems, contributing to the advancement of sustainable and efficient energy technologies.